2019
DOI: 10.3389/fphys.2019.00511
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Endothelial Mechanical Sensing and Signaling, a Story of Focal Adhesions and Integrins in Ventilator Induced Lung Injury

Abstract: Patients with critical illness such as acute lung injury often undergo mechanical ventilation in the intensive care unit. Though lifesaving in many instances, mechanical ventilation often results in ventilator induced lung injury (VILI), characterized by overdistension of lung tissue leading to release of edemagenic agents, which further damage the lung and contribute to the mortality and progression of pulmonary inflammation. The endothelium is particularly sensitive, as VILI associated mechanical stress resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…In particular, the intracellular skeletal structures, such as stress fibers and focal adhesions, are expected to be involved in the transmission of various cellular stimuli that connect the external environment to the inside of the cell. Based on the hypothesis that stress fibers and focal adhesions function as receptors for various stimuli [14][15][16], we focused on the localization and morphological changes of the component proteins of these structures associated with electrical stimulation.…”
Section: Electrical Stimulation Of the Cellsmentioning
confidence: 99%
“…In particular, the intracellular skeletal structures, such as stress fibers and focal adhesions, are expected to be involved in the transmission of various cellular stimuli that connect the external environment to the inside of the cell. Based on the hypothesis that stress fibers and focal adhesions function as receptors for various stimuli [14][15][16], we focused on the localization and morphological changes of the component proteins of these structures associated with electrical stimulation.…”
Section: Electrical Stimulation Of the Cellsmentioning
confidence: 99%
“…1 The direct measurement of the vascular strain in the lung is difficult and has not yet been reported. 2 Tschumperlin et al correlated the lung expansion during breathing with an increase in the epithelial cell surface. 3,4 Although the extent of the stretch that pulmonary microvascular cells undergo is not determined yet, in vitro studies aimed at investigating endothelial cell mechanotransduction have adopted epithelial stretch values.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies are indicating that integrins could represent biochemical and mechanical sensors to respond to and interact with ECM of differing properties 38 , 39 . Ding X et al 40 and Kelly GT et al 41 found that integrins are critical mechanical sensors to mediate VILI. In our previous study we found that integrin β3 upregulation was involved in lipopolysaccharide -induced pulmonary fibrosis 42 .…”
Section: Discussionmentioning
confidence: 99%